Analysis Of Operational Performance And Price Of Penataran Train On Surabaya City – Blitar Route - Fadli Rozaq; Nanda Ahda Imron; Rachmat Agil; Muchlisin muchlisin (Politeknik Perkeretaapian Indonesia Madiun, 2022)
The Penataran Train is the train that has the highest passenger volume among the Local Economy Trains in East Java Province. The Penataran train is very much needed by people, but if the operational and management is not handled properly, it may affect on the effectiveness and efficiency of the transportation system as a whole. Operational performance assessment is needed to improve the services to users of the Penataran Train in the future. Operational performance was assessed on several aspects, including load factor, travel time, frequency, headway, and ticket prices. The purpose of this study was to analyze the operational performance and prices of the Penataran Train on Surabaya City – Blitar route. The results showed that the average load factor was 61% and met the standard of SE No. 24 of 2020. The average rate of the train arrival time of 99% was in accordance with the SIPOKA standard. In contrast, the average rate of departure time of 83% was not in accordance with the SIPOKA standard. The frequency of 8 trips per day with a headway of 198.75-202.25 minutes was not meet the standards in KM No. 22 of 2003. The point of intersection between the respondents' ATP and WTP was at a price following the ticket price stipulated in PM No. 21 of 2020, which was Rp10,001–Rp15,000